2021
DOI: 10.1016/j.ijid.2020.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic COVID-19 in hospital visitors: The underestimated potential of viral shedding

Abstract: Highlights In one day, 4% (6 in 150) of hospital visitors had asymptomatic COVID-19. Potential of visitors’ viral shedding in healthcare facilities is underestimated. SARS-CoV-2 introduction into facilities is not fully blocked by universal masking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
0
14
0
3
Order By: Relevance
“…Because asymptomatic health care workers might contribute to disease spread in and out of hospitals, surveillance of asymptomatic individuals is important for infection control and transmission reduction in health care settings and community. 116 , 117 Meanwhile, hand hygiene and personal protective equipment were necessary for hospital visitors. 117 A previous study showed that most asymptomatic patients belong to younger groups, 3 which was consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because asymptomatic health care workers might contribute to disease spread in and out of hospitals, surveillance of asymptomatic individuals is important for infection control and transmission reduction in health care settings and community. 116 , 117 Meanwhile, hand hygiene and personal protective equipment were necessary for hospital visitors. 117 A previous study showed that most asymptomatic patients belong to younger groups, 3 which was consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Visitors were also limited in the inpatient units, clinics, and emergency departments at this time, further limiting the possibility of transmission of COVID-19. One study showed that almost 4% of asymptomatic visitors to the hospital were positive for COVID-19, highlighting the importance of visitor restriction [ 34 ]. In addition, screening protocols, universal masking, strict PPE protocols, and frequent cleaning procedures were implemented throughout the different areas of the hospital and clinic per CDC guidelines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating asymptomatic prevalence of COVID-19 among family/essential caregivers who had screened negative for symptoms ranged from 4 to 10% in studies from Brazil and New York. 10,11 However, this data was obtained during periods of high community prevalence of SARS-CoV-2 and prior to the adoption of public masking in New York. Furthermore, given the lack of access to testing for the general public early in the pandemic, it is possible that many individuals that tested positive had old infections, and were no longer communicable, despite positive RT-PCR testing.…”
Section: Covid-19mentioning
confidence: 99%